(untitled) (Journal of Engineering, 2010)
The aim of this paper is to evaluate the effect of the converter system on the power factor of the supply network .Therefore a 3-phase, 6-pulse , bridge converter is assembled and connected to a power supply through a 3-phase ac voltage regulator .The theoretical analysis is simulated using Fourier series analysis and Fast Fourier Transform ( FFT ) algorithm . The experimental measurements of distortion factor , displacement factor and total power factor are recorded . The experimental results are shown to be coincident with the theoretical results. The consideration of power factor improvement relative to distortion and displacement factors is discussed.